Comparison of methodological quality between the 2007 and 2019 Canadian dietary guidelines. Issue 16 (17th November 2020) - Dai, Zhaoli; Kroeger, Cynthia M; Lawrence, Mark; Scrinis, Gyorgy; Bero, Lisa
Abstract: Objective: With significant shifts in the dietary recommendations between the 2007 and 2019 Canadian dietary guidelines, such as promoting plant-based food intake, reducing highly processed food intake and advocating the practice of food skills, we compared their differences in guideline development methods. Design: Two reviewers used twenty-five guided criteria to appraise the methods used to develop the most recent dietary guidelines against those outlined in the 2014 WHO Handbook for Guideline Development. Setting: Canada. Participants: 2007 and 2019 dietary guidelines. Results: We found that the 2019 guidelines were more evidence-based and met 80 % (20/25) of the WHO criteria. For example, systematic reviews and health organisation authoritative reports, but not industry reports, constituted the evidence base for the dietary recommendations. However, recommendations on food sustainability and food skill practice were driven primarily by stakeholders' interests. By contrast, less information was recorded about the process used to develop the 2007 guidelines, resulting in 24 % (6/25) consistency with the WHO standards. Conclusions: Our analysis suggests that a more transparent and evidence-based approach is used to develop the 2019 Canadian dietary guidelines and that method criteria should support further incorporation of nutrition priorities (food sustainability and food skills) in future dietary guideline development.